Clinical evaluation of a novel H. pylori fecal molecular diagnosis kit (multiplex RT-PCR method) for detecting clarithromycin and fluoroquinolones resistance using stool samples - Wei, Wen-juan; He, Bang sun; Lv, Bin; Yang, Bin; Xie, Yong; Zhang, Zhen yu (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHelicobacter pylori infection poses a significant global health challenge, exacerbated by rising antibiotic resistance. This study aimed to evaluate a novel multiplex RT-PCR-based fecal diagnostic kit (Cowin Biosciences, Jiangsu, China) for detecting mutations in the 23S rRNA and gyrA genes associated with clarithromycin and fluoroquinolone resistance in H. pylori.MethodsA total of 1,176 participants from four clinical centers in China were enrolled between August 2022 and October 2023. Phenotypic resistance was assessed on H. pylori isolated from gastric samples using the minimum inhibitory concentration (MIC) method (E-test), while fecal samples were analyzed molecularly via the diagnostic kit and Sanger sequencing. Positive (PPA), negative (NPA), and overall percentage agreement (OPA) with 95% confidence intervals (CI) were calculated.ResultsThere was a high level of consistency between phenotypic testing and novel diagnostic kit. The PPA, NPA, and OPA of the fecal diagnostic kit for detecting clarithromycin susceptibility were 92.97% (CI: 90.6%-95.3%), 87.89% (CI: 85.0%-90.8%), and 90.36% (CI: 88.5%-92.3%), respectively. And likewise, the PPA, NPA, and OPA in diagnosing H. pylori resistance to fluoroquinolones were 86.85% (CI:83.6%- 90.1%), 91.12% (CI: 88.6%-93.7%), and 89.12% (CI: 87.1%-91.1%), respectively. Beyond that, the diagnostic kit also exhibited a high degree of concordance with the outcomes of Sanger sequencing. Specifically, when assessing clarithromycin resistance, the PPA, NPA, and OPA of the diagnostic kit were 97.13% (CI: 95.7%-98.6%), 94.62% (CI: 92.6%-96.6%), and 95.90% (CI: 94.7%-97.1%), respectively. Similarly, application of the diagnostic kit to detect fluoroquinolone resistance achieved a PPA of 96.92% (CI: 94.9%-98.4%), an NPA of 93.18% (CI: 91.0%-95.3%), and an OPA of 94.69% (CI: 93.3%-96.1%). The concordance rate between the fecal kit and phenotypic susceptibility testing varied with MIC values. For clarithromycin resistance, the positive percentage agreement (PPA) was lowest (89.74%) when MIC exceeded 256 µg/mL but peaked at 96.47% for MIC values between 32 and 256 µg/mL. The highest overall concordance (Kappa = 0.774) was observed at intermediate MIC levels (4–32 µg/mL), suggesting optimal detection accuracy in this range.ConclusionsThe fecal diagnostic kit provides a rapid, non-invasive, and reliable method to predict clarithromycin and fluoroquinolone resistance, supporting personalized therapy.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT05410652.